UMPSA conducts validation audit for offshore programmes at Muscat College - Nor Ilma, Mustafa Kamal (UMPSA, 2023)
OMAN, 19 December 2023 - The delegation of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) held a validation audit of the UMPSA offshore programmes conducted by Muscat College, Oman.